Urgency Of Organizational Change Management In Islamic Educational Institutions In Indonesia - Wahab, Abdul Fattah; Suprayogo, Imam; Tharaba, M. Fahim (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2023)
Educational institutions, both existing and newly established, require organizational change/development studies that are relevant to maintaining their existence. There is cross-role (interplay) between individuals as part of society and organizations, organizations as part of society, and society itself as a formation of various 'organizational backgrounds. So that changes in society demand organizational changes, including educational organizations. Change will not occur unless the need for change is critical. Organizational change is a change related to development, as well as improvements, and adjustments that include the structure, technology, work methods, and management system of an organization. the study of problematic Islamic educational institutions in Indonesia divides into three perspectives: ontological, epistemological, and axiological. In this reality, it becomes important to examine the urgency of organizational change management of Islamic educational institutions as a comprehensive study so that they are able to answer the challenges of the times and make the best possible utilization of their organizational potential. In this research, the author uses a content analysis approach model. This study's data sources include journals, papers, and books about literacy about change management, organizational behavior, and Islamic educational institutions